Toxicokinetics of sediment-associated polybrominated diphenylethers (flame retardants) in benthic invertebrates (Lumbriculus variegatus, oligochaeta) - Leppänen, Matti T.; Kukkonen, Jussi V. K. (Environmental toxicology and chemistry, 2004)
Polybrominated diphenylethers (PBDEs) are ubiquitous environmental contaminants showing rapid temporal increase in some sample types. The compounds are known to biomagnify in aquatic food webs and are assumed to archive into sediments and soils. Currently, no direct evidence indicates whether sediment‐associated PBDEs are available for biota. The aim of the present study was to explore the uptake and elimination of two common congeners (47 and 99) in sediment‐inhabiting invertebrates to shed light on possible bioavailability of sediment‐associated PBDEs. Two clean lake sediments were spiked with environmentally relevant concentrations of 14C‐labeled tetra‐ and pentabromo diphenylether, and oligochaetes (Lumbriculus variegatus) were exposed for three or four weeks to allow kinetic accumulation calculations. Subsequent depuration tests were performed after three weeks of exposure to obtain depuration rates. Both congeners were clearly bioavailable, and only slight differences in steady‐state tissue concentrations were found between the four sediment‐ingesting oligochaete treatments (biota sediment accumulation factors [BSAFs], 3.0–3.7). The tetrabromo diphenylether‐exposed oligochaetes that did not ingest sediment had clearly lower influx rates (0.1 vs 1–3 nmol h‐1) than sediment‐ingesting worms. Also, the estimated BSAF (1.8) was statistically different from that of the sediment‐ingesting oligochaetes. These findings support the significance of feeding behavior in bioaccumulation of very hydrophobic organic contaminants. Depuration of both congeners was biphasic, indicating two kinetically different compartments in L. variegatus. Compartment A made up 73 to 92% of total radioactivity in tissues and had relatively fast depuration rates (half‐lives, 10.5–47.5 h); the smaller compartment B had very slow depuration rates. No significant biotransformation of PBDEs was evident. The present study clearly demonstrates that the sediment‐associated PBDEs, like other hydrophobic organic contaminants of environmental concern, are not totally sequestered from sediment‐inhabiting oligochaetes and are subject to trophic transfer.